Experimental Research on Coal and Gas Delay Outburst and AE Characteristics under Conditions of Geostress and Gas Pressure Disturbance. (25th August 2021) - Jiabo, Geng; Jiangtong, Liu; Xiaoshuang, Li; Wen, Nie; Dongming, Zhang; Jiang, Xu
Abstract : Adopting yellow mud as barrier layer materials, coal and gas delay outburst experiments under conditions of geostress and gas accumulation disturbance were carried out by using self-developed simulation system, to find out roles of geostress and gas pressure played in the process of the delay outburst and ways to predict it, through analysis of variations of gas pressure, and AE characteristics during the process. The results show that after the geostress increased by 0.11 MPa from 1.80 MPa, an outburst occurs, while in gas accumulation situations, the gas pressure increase of 0.27 MPa from 0.67 MPa induces an outburst; hence, geostress is one of the dominant factors impacting an outburst occurrence. The lasting time of the outburst triggering under geostress disturbance is shorter than that under gas accumulation disturbance, while the duration of the outburst development under gas accumulation conditions is longer than that under geostress conditions. Coal seam breakage by geostress is the precondition for an outburst risk, and gas expansion energy is the dominant parameter influencing the duration of the outburst development. The AE signals show distinctive features in different stages of the outburst under geostress disturbance. At the preparation stage of the outburst, the AE signals increase sharply but have a low intensity and then drop to a lower balance level. At the triggering stage, the AE signals become active and increasing until up to the peak where the outburst occurs, and the intensity is highest.